(untitled) (Constructionism Conference Proceedings, 2025)
In the scope of the new technological era we live in, creative learning, prototyping and innovative problem solving are increasing in value day by day; revealing a significant lack of knowledge between theoretical knowledge and practical application in mechanical systems. Due to this, newcomers in K12 laboratories find it quite challenging to take on new projects by themselves. Aiming to find a constructive way to fill this gap, we prototyped hands-on kits called “automata”. The kits we designed in total have 6 models, completely open-sourced, which we produce in our fablab consisting of a farm of 20+ 3D printers. The kits illustrate core concepts of cams, cranks and gears, each model has its own original design which illustrates systems we constantly face in our daily lives but fail to realize. To encourage innovative and creative thinking, we enhanced the kits with augmented reality (AR) by creating our own website, “AutomatAR”. As users interact with these models, movements are mirrored by corresponding AR animations on their mobile devices. Users overcome our AR scenarios, case studies, then generate their own case studies with, again, our own AI website. We had the opportunity to test this kit on K12 students, each workshop resulting with high accuracy of learning in our feedback forms. We believe this workshop is a great contribution to constructionist and innovative learning since by connecting physical building with digital visualization, the kit offers an interactive approach to learning mechanics, helping K12 students to bridge the gap between theory of mechanics and the practical technological application.